Design of storage box for unmanned aerial vehicle - Ang, Jun Ping (2018)
This paper illustrates the background of unmanned aerial vehicle and how this technology has commercialized and function as a method for delivery services. Through critical study and research carried out on various materials and different types manufacturing methods. It shows the comparison between three different materials and determine the suitable material for the creation of a storage box. The report introduces the process on selection of hardware devices, to bring out the potential of the automated storage box physically, and the creation of software program that allows the storage box to function automatically. Covering the initial phase of the planning to the construction of the prototype. The author will design and build a storage box different from the current market designs for a standard drone